2007
DOI: 10.1002/bmc.861
|View full text |Cite
|
Sign up to set email alerts
|

Identification of estrogenic/anti‐estrogenic compounds in diesel exhaust particulate extract

Abstract: Diesel exhaust particulate extract (DEPE) was obtained from diesel exhaust particulates with Soxhlet extraction using dichloromethane. After separating DEPE into 11 fractions by liquid-liquid extraction, the neutral fraction (N) showed anti-estrogenic activity and the weak acid (phenol) fraction (WA(P)) showed estrogenic and anti-estrogenic activities by a yeast two-hybrid assay system expressing human estrogen receptor alpha. Both fractions were thoroughly fractionated by silica gel column chromatography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…contained in PM, especially from diesel exhaust [12,13], are described in the literature as endocrine disruptors with either estrogenic, antiestrogenic or anti-androgenic activity [14,[77][78][79][80][81]. Kizu et al described anti-androgenic activity of certain particle compounds from diesel exhaust in human PC3/ AR cells derived from prostate cancer tumors [15], while Okamura et al reported anti-estrogenic activity of similar compounds in human MCF-7 cells from breast cancer tumors [14].…”
Section: Action As Endocrine Disruptorsmentioning
confidence: 99%
“…contained in PM, especially from diesel exhaust [12,13], are described in the literature as endocrine disruptors with either estrogenic, antiestrogenic or anti-androgenic activity [14,[77][78][79][80][81]. Kizu et al described anti-androgenic activity of certain particle compounds from diesel exhaust in human PC3/ AR cells derived from prostate cancer tumors [15], while Okamura et al reported anti-estrogenic activity of similar compounds in human MCF-7 cells from breast cancer tumors [14].…”
Section: Action As Endocrine Disruptorsmentioning
confidence: 99%
“…Sources of these chemicals in the marine environment include direct input from combustion [1] and sewage effluents [7]. Parent PAH released into the environment can also undergo oxidation as a result of thermal and ultraviolet irradiation [8].…”
Section: Introductionmentioning
confidence: 99%
“…PAH exposure has also been linked to community-level toxic effects such as reduced viability and food web disruption [4]. In addition to being good model compounds and abundant in the environment, PY and PYOH also exhibit many of these toxicities [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscellaneous compounds found in DEP are among endocrine impairing chemicals, which exhibit estrogenic and anti-androgenic activities [2][3][4][5] . DEP compounds were reported to have adverse effects on reproductive system and impair both reproductive and endocrine functions in male mice and rats [6,7] .…”
Section: Introductionmentioning
confidence: 99%